TRANSFORMATION OF THE INSTITUTIONAL ENVIRONMENT OF INNOVATIVE DEVELOPMENT OF THE PUBLIC ECONOMY (INNOVATIVE ECONOMY, 2024)
Tymoshchuk V.V. TRANSFORMATION OF THE INSTITUTIONAL ENVIRONMENT OF INNOVATIVE DEVELOPMENT OF THE PUBLIC ECONOMYPurpose. The aim of the article is to generalize the trends of the transformation of the institutional environment of the innovative development of the national economy and the features of the institutional support for the development of innovations.Methodology of research. The theoretical and methodological basis of the research is: a systematic approach to the generalization of trends in the transformation of the institutional environment of innovative development; institutional approach to the substantiation of the elements of the regulatory influence of formal norms, oriented towards the development of innovations; structural and functional analysis – to determine the macroeconomic and microeconomic manifestation of post-industrial transformations on the institutional environment.Findings. It is emphasized that for the formation of an effective toolkit for innovative modernization of the national economy, it is important to take into account global factors of economic dynamics, their exogenous and endogenous manifestations. It was established that the modern vector of global transformations, which is already having an impact on the national economy, has become digital modernization, which radically changes the economic relationships of people and the fundamental role of economic resources.It is argued that digitalization generates effects that receive macroeconomic manifestation through the emergence and spread of new business strategies, changes in market conditions, and an increase in labour productivity. At the microeconomic level digitalization leads to a change in the structure and supply of goods production, their quality, logistics and sales conditions, and the interaction of manufacturers. Digital technologies contribute to the emergence of new institutions and institutes and influence existing ones by algorithmizing institutional influence and regulation, minimizing the impact of institutional traps and preventing the emergence of new ones, reducing the stability of existing routines, increasing or decreasing the effectiveness of institutions.Originality. It is substantiated that the post-industrial transformations of the economy and the institutional environment change the structural characteristics, but not the essential purpose of institutions and institutes in innovative development. The processes of digitalization and network interactions contribute to the standardization and algorithmization of institutes, the introduction of "digital institutes"; increase the efficiency of established institutes and institutions; create new dysfunctions due to the opportunistic behaviour of economic subjects; form an institutional "vacuum" due to the proliferation of digital technologies that have not yet become embedded in the institutional environment.In view of the task of innovative modernization of the public economy, in order to exclude the negative impact it is necessary to modernize the institutional environment itself to change the direction of the functional influence of regulatory norms and introduce organizational innovations that can improve the institutional structure.Practical value. The theoretical and methodological provisions of the study deepen the practical principles and tools of institutional regulation of innovative modernization of the national economy.Key words: modernization, innovative development, social economy, transformation, institutional regulation, institute, institution.
Keywords: modernization; innovative development; social economy; transformation; institutional regulation; institute; institution.